INOVASI PEMBUATAN JAM DIGITAL RUNNING TEXT BAGI PERANGKAT DESA DI BALAI DESA MANUNGGAL - Khoirun Nisa'; Wahyudi Wahyudi; Muhammad Saat Ibnu Waqfin; Bambang Rianto; Hellyou Susanti; Siti Khalimatus Sa'diah; Lutfiah Khoirunnova; Moh Zuem Marzuki; Muhammad Iqbal Nasrullah (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
In today's digital information era, effective and efficient communication is the main key to conveying messages to the public. One of the increasingly popular communication media is Running Text, or what is often called running text. The work program for making Running Text is a program that is part of the community service program. The purpose of this program is to optimize the use of technology and increase the use of technology in the daily lives of village communities, encouraging adaptation to increasingly rapid digital developments. There is also a reason why the work program for making Running Text is as a digital clock and display of village hall information, so that the wider community can obtain information about the existence of the Manungal village hall. The flexibility of using Running Text, which is updated in real time and can be adjusted to the needs of the main hall, makes it a flexible medium for various types of information, from routine announcements to urgent notifications. The method applied in this service includes three main stages, namely design, implementation, and evaluation. Design is the process of work or design used to design a design object. In designing Running Text, the first step is to identify the main purpose of the information to be conveyed. Running Text is used to convey short and precise information. The sentences used must be short but informative, and use language that is easily understood by the community. The implementation of this community service program has succeeded in achieving the desired goals. The following are some of the results that have been achieved in the implementation of this community service program: Increasing Access to Information, Utilization of Digital Technology, Cost Savings by the village hall, and Increasing Time Awareness.